Reduced description of multi-particle systems with continuous random correlation - Kotlyarov , O. L. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
For a system of identical particles, described by stochastic differential equations of the continuous type, we derive a kinetic equation and equations for statistically independent Markov limit trajectories of the particles.